The Therapeutic Potential of Angiotensin-converting Enzyme and Angiotensin Receptor Inhibitors in the Treatment of Colorectal Cancer: Rational Strategies and Recent Progress - Asgharzadeh, Fereshteh; Hassanian, Seyed M.; Ferns, Gordon A.; Khazaei, Majid; Hasanzadeh, Malihe (Current Pharmaceutical Design, 2018)
Colorectal cancer (CRC) is one of the most common causes of cancer-related death in the world. There is a document that angiotensin (AT) which is found to be involved in the progression of CRC. Furthermore, Angiotensin receptor inhibitors (ARIs) and angiotensin-converting enzyme Inhibitors (ACE-Is) demonstrate activity in CRC by their inhibition of both Insulin-like growth factor 1 (IGF-1) and Vascular endothelial growth factor (VEGF), and therefore present a potentially novel therapeutic strategy in colorectal cancer, which have summarized in the current review. Preclinical studies have illustrated the direct effect of major active mediator angiotensin II (ATII) on the promotion of angiogenesis through VEGF and other proliferative mediators. Suppression of the angiotensin II type I receptor (AT1R) via ACE-Is has shown a reduction in the development of solid tumor and metastasis, particularly CRC incidence, polyp formation, and distant metastasis. MicroRNAs (miRs) are a family of small nucleotides without coding that plays an important role after transcribing hundreds to thousands of non-coding and coding gene. Against this background, the application of anti-hypertensive medications such as losartan might have a therapeutic impact, although further preclinical and clinical studies might provide novel insight into the potentially beneficial effect of ACE-Is in the treatment of colorectal cancer patients.
Keywords: cancer-related death